Comparison of four surgical approaches for rectal prolapse: multicentre randomized clinical trial. Issue 1 (19th January 2022) - Smedberg, J.; Graf, W.; Pekkari, K.; Hjern, F.
Abstract: Background: Several different procedures have been described for surgical treatment of rectal prolapse and consensus on the optimal approach has not been reached. The Swedish Rectal Prolapse Trial was performed with the aim to compare the outcomes after the most common surgical approaches to rectal prolapse. Method: A multicentre randomized trial was conducted from 2000 to 2009. Patients were randomized between a perineal or an abdominal approach for correction of rectal prolapse (randomization A) if eligible for any procedures. Patients considered unsuitable for random allocation were only included in randomizations B or C. Patients in randomization B (perineal group) were randomized to Delorme's or Altemeier's procedures and those in randomization C (abdominal group) to suture rectopexy or resection rectopexy. Primary outcomes were bowel function and quality of life, measured using Wexner incontinence score and RAND-36, and secondary outcomes were complications and recurrence at 3 years. Results: During the study period, 134 patients were randomized: 18 in randomization A group, 80 in randomization B group and 54 in randomization C group; of these, 122 patients underwent surgery. Mean follow-up was 2.6 years. Improvements in Wexner and RAND-36 scores were seen but with no significant difference between the groups. Health change scores were significantly improved from baseline up to 1 year after surgery ( P < 0.001). At 3 years, recurrence rates were two of seven patients for abdominal versus five of eight patients for perineal approach ( P = 0.315), 18 of 31 patients (58 per cent) for Delorme's versus 15 of 30 patients (50 per cent) for Altemeier's ( P = 0.611) and four of 19 patients (21 per cent) for suture rectopexy versus two of 21 patients (10 per cent) for resection rectopexy ( P = 0.398). There were no significant differences regarding postoperative complications. Conclusion: For all procedures, significant improvements from baseline in health change scores were noted after surgery. Recurrence rates were higher than previously reported. Registration number: NCT04893642 (http://www.clinicaltrials.gov ). Abstract : The Swedish Rectal Prolapse Trial was performed with the aim to compare bowel function, quality of life, recurrence rates and complications after randomization of common surgical methods for rectal prolapse. For all patients together, significant improvements from baseline in incontinence and health change scores were noted. Abdominal procedures resulted in lower recurrence rate than perineal procedures. Overall, recurrence rates were higher than previously reported.